Endoscopic Endonasal Versus Transoral Odontoidectomy for Non-Neoplastic Craniovertebral Junction Disease: A Case Series. Issue 6 (30th August 2021) - Heller, Robert S; Glaspy, Tyler; Mhaskar, Rahul; Bhadelia, Rafeeque; Heilman, Carl B
Abstract: BACKGROUND: Odontoidectomy is a challenging yet effective operation for decompression of non-neoplastic craniovertebral junction disease. Though both the endoscopic endonasal approach (EEA) and the transoral approach (TOA) have been discussed in the literature, there remain few direct comparisons between the techniques. OBJECTIVE: To evaluate the perioperative outcomes of EEA vs TOA odontoidectomy. METHODS: A retrospective review of all cases undergoing odontoidectomy by either the EEA or TOA was performed. Attention was paid to the need for prolonged nutritional support, prolonged respiratory support, and hospitalization times. RESULTS: During the study period between 2000 and 2018, 25 patients underwent odontoid process resection (18 TOA and 7 EEA). The most common indication for surgery was basilar invagination. Hospital length of stay, intensive care unit length of stay, and intubation days were all significantly shorter in the EEA group compared to the TOA group ( P < .01, P = .01, P < .01, respectively). Prolonged nutritional support in the form of a gastrostomy tube was required in 5 patients and tracheostomy was required in 4 patients; all of these underwent odontoidectomy by the TOA. There was no statistical difference in neurological outcomes between the EEA and TOA groups ( P = .17). CONCLUSION: Odontoidectomy can be performed safely through both the EEA and TOA. The results of this study suggest the EEA has shorter hospitalizations and a lower probability of requiring prolonged nutritional support. These advantages are likely the results of decreased oropharyngeal mucosa disruption as compared to the TOA.